Development, Training, Performance Assessment And Employee Achievement (A Literature Review) - RR Fera Pratiwi; Adhitya Pranajati; Desi Nursanti; Fani Pangabdian; Inggar Bagus Wibisono; Tresya Lien Matakupan; Johann Amadeus Albert Tokoro; Michael Willian Ramschie; Mira Veranita (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
The era of globalization requires companies including hospitals to improve their services. One of them is to improve the management of the company's human resources (HR), because HR is considered an invaluable organizational asset. The company is responsible for improving the abilities and competencies of employees through development programs, performance appraisals, and achievement appraisals. This article aims to evaluate literature related to the implementation of development and training programs, employee performance appraisal methods, and employee achievement appraisal methods. This study uses a literature review by searching research journals using Google Scholar with keywords such as development management, training, performance, and HR achievements in Indonesian and English. The results show that employee development and training must be tailored to the needs, goals, and facilities of the company, and require periodic evaluations to improve employee performance and ultimately work performance. There are various methods of performance appraisal, including the Analytical Hierarchy Process (AHP) method which uses criteria such as discipline, achievement, responsibility, and field competence. In conclusion, this employee performance and achievement appraisal will help the company in making decisions related to employee promotion, dismissal, or mutation.